E-cigarettes and equity: a systematic review of differences in awareness and use between sociodemographic groups. Issue Volume 26:Issue e2(2017) (21st December 2016) - Hartwell, Greg; Thomas, Sian; Egan, Matt; Gilmore, Anna; Petticrew, Mark
Abstract : Objective: To assess whether electronic cigarette (e-cigarette) awareness, 'ever use' and current use vary significantly between different sociodemographic groups. Design: Systematic review. Data sources: Published and unpublished reports identified by searching seven electronic databases (PubMed, MEDLINE, Web of Science, EMBASE, Global Health, PsycINFO, CINAHL Plus) and grey literature sources. Study selection: Systematic search for and appraisal of cross-sectional or longitudinal studies that assessed e-cigarette awareness, 'ever use' or current use, and included subgroup analysis of 1 or more PROGRESS Plus sociodemographic groups. No geographical or time restrictions imposed. Assessment by multiple reviewers, with 17% of full articles screened meeting the selection criteria. Data extraction: Data extracted and checked by multiple reviewers, with quality assessed using an adapted tool developed by the Joanna Briggs Institute. Data synthesis: Results of narrative synthesis suggest broadly that awareness, 'ever use' and current use of e-cigarettes may be particularly prevalent among older adolescents and younger adults, males, people of white ethnicity and—particularly in the case of awareness and 'ever use'—those of intermediate or high levels of education. In some cases, results also varied within and between countries. Conclusions: E-cigarette awareness, 'ever use' and current use appear to be patterned by a number of sociodemographic factors which vary between different countries and subnational localities. Care will therefore be required to ensure neither the potential benefits nor the potential risks of e-cigarettes exacerbate existing health inequalities.